"Min favoritfigur är Maria Gripe. Är det okej om jag kallar henne Gibban?": Ett medforskande litteratursamtal kring Maria Gripes I vår lilla stad-trilogi - Hellström, Martin (Tidskrift för litteraturvetenskap, 2016)
”My favorite character is Maria Gripe. Is it okay if I call her Gibban?” Co-Researching Literary Conversations about Maria Gripe’s I vår lilla stad Trilogy This article studies Maria Gripe’s firtst three novels, I vår lilla stad (In Our Little Town, 1954), När det snöade (When it Snowed, 1955) and Kung Laban kommer (King Laban Comes, 1956). The study involves a group of children, all of whom have read these works, and describes a method that facilitates the use of children’s interpretations of children’s literature within the field of academic literary studies. As a point of departure, the method focuses on the standpoints found within the field of Citizen Science, which allows people outside academia to contribute to science through their own experiences. In this case, this concerns the experience of being a child and being part of the target group for the texts used in this study. Aidan Chambers’ ”book talk” method was used to gather the children’s interpretations of the works. Conversations were recorded and transcribed, and interpretations were put together through quotations from the dialogues, and via summaries and analyses of the book talks. With regard to Maria Gripe’s first three works, Chambers’ book-talk method (whereby students take an active part in the research) revealed that the violation of genre-conventions in these works lead to an insecurity on the part of the reader; namely, readers weren’t sure how to approach the works. Previous research and reviews have claimed that these works are unoriginal in relation to other stories with live cuddly toys. By contrast, Chambers’ book-talk method illustrates that, in the first part of the trilogy, Gripe’s violation of the division into separate episodes (in favor of a detective plot) generates confusion on the part of the reader regarding which genre the work falls into. It also leads to difficulties in understanding whether, for instance, the animals are to be regarded as speaking animals, or as living cuddly toys. This article is the first result of a long-term study which intends to analyze Gripe’s authorship in its entirety through Chambers’ version of book talks.